Modelling financing mechanisms using mini bonds for green and zero-waste projects - Bužinskė, Julija; Nguyen, Thanh Hung; Zopiatis, Anastasios; Stankevičienė, Jelena (My University, 2025)
Purpose – To close the gap in scientific literature and practice of applying green finance instruments, such as green mini-bonds, for financing environmentally beneficial projects with the practical application case of municipal waste reduction. Design/methodology/approach – It follows a case study and scenario analysis to investigate the financing options for green and zero-waste projects. Data for the analysis has been collected from the financial reports of waste management companies for the years 2016–2020, operating in the ten counties of Lithuania. Five scenarios have been developed for the study – financing of large-scale projects with company funds, loan financing, EU funds orsubsidies, municipal green bond issuance and mixed financing. The investment analysis relies on the cost-benefit analysis principles recommended by the European Commission. Findings – The research shows that the issuance of green mini-bonds can serve as an alternative to the funding with the EU funds, delivering the same economic benefits and providing better financial performance. Analysis also shows that the issuance of green mini-bonds is the most favourable financing option. Research limitations/implications – Furtherresearch can be expanded with the analysis of other municipalities in Lithuania to test the relevance of the accuracy of the conceptual model. Practical implications – Results also show that small issuers, such as municipalities or waste management companies, can create value and cover their financing needs. As a result, municipalities can consider the issuance of mini-bonds to fund environmentally friendly projects. Originality/value – The research provides alternatives to traditional financing ways such as bank loan financing. A new economic model of scenarios for municipal waste management was developed, and its effectiveness was evaluated.
Keywords: Mini-bonds; Municipal solid waste; Sustainable finance; Green finance; Green bonds; Green investments; Cost-benefit analysis; Waste management